Development and Implementation of Strategic Reading Intervention in Remedial Program: A Quasi-Experimental Study of Left behind Filipino Learners - Jordan Miranda Pocaan; Lyndon Lucila Bailon; Jean Pauline Trilles Pocaan (Lingua Cultura, 2023)
The research aimed to develop an effective strategic reading intervention for remedial programs to aid the reading gaps of the left behind grade 5 learners. To realize education for all, teachers and school leaders should provide effective interventions targeting students’ interests and weaknesses. It used a quasi-experimental approach to determine the reading ability of 38 struggling readers in terms of word recognition, reading comprehension, and reading speed using reading stories, Dolch’s basic sight words, and the Phil-IRI Manual 2018. The research developed strategic reading intervention materials to support teachers and students during the remedial programs. The pre-tests revealed that the reading ability of the struggling readers was at a frustration level. Furthermore, the developed strategic intervention reading materials used in remedial programs were composed of four parts: learning content, learning task guide, assessment guide, and enhancement guide. The post-tests showed that the participants’ reading ability progressed to instruction and independence levels after the remedial program. It is concluded that determining the student’s present ability is beneficial to develop effective intervention materials. It is suggested that school leaders and program specialists should develop faculty and student support programs ideally to uplift the student’s literacy.